2009
DOI: 10.2193/2008-265
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Mediated Moose Survival in Northeastern Minnesota

Abstract: The earth is in the midst of a pronounced warming trend and temperatures in Minnesota, USA, as elsewhere, are projected to increase. Northern Minnesota represents the southern edge to the circumpolar distribution of moose (Alces alces), a species intolerant of heat. Moose increase their metabolic rate to regulate their core body temperature as temperatures rise. We hypothesized that moose survival rates would be a function of the frequency and magnitude that ambient temperatures exceeded the upper critical tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(165 citation statements)
references
References 209 publications
4
154
1
Order By: Relevance
“…However, while free-ranging moose in the southern range commonly experience conditions above the reported temperature thresholds, predicted behavioural responses to climate (i.e., use of shelter, reduced activity) have not been observed consistently (Dussault et al 2004;). On the other hand, moose survival and population growth are negatively correlated with temperature extremes in Minnesota Lenarz et al 2008), adding some credence to the direct effects hypothesis. Alternatively, warming temperatures are known to favour white-tailed deer expansion into moose range, and increased transmission of deer parasites (the brainworm Parelaphostrongylus tenuis Dougherty, 1945, the tick Dermacentor albipictus Packard, 1869, the fluke Fascioloides magna Bassi, 1875) to moose may invoke substantial population losses (Lankester 2010).…”
Section: Population Demography In Ontariomentioning
confidence: 89%
See 1 more Smart Citation
“…However, while free-ranging moose in the southern range commonly experience conditions above the reported temperature thresholds, predicted behavioural responses to climate (i.e., use of shelter, reduced activity) have not been observed consistently (Dussault et al 2004;). On the other hand, moose survival and population growth are negatively correlated with temperature extremes in Minnesota Lenarz et al 2008), adding some credence to the direct effects hypothesis. Alternatively, warming temperatures are known to favour white-tailed deer expansion into moose range, and increased transmission of deer parasites (the brainworm Parelaphostrongylus tenuis Dougherty, 1945, the tick Dermacentor albipictus Packard, 1869, the fluke Fascioloides magna Bassi, 1875) to moose may invoke substantial population losses (Lankester 2010).…”
Section: Population Demography In Ontariomentioning
confidence: 89%
“…Although moose population size and distribution have varied substantially in the last century, recent declines seem to be associated primarily with climate change and its effect on survival and productivity. The mechanism by which moose succumb to climate effects remains to be fully elucidated but seems related either to direct effects of heat stress on susceptibility to mortality and reduced productivity Lenarz et al 2008Lenarz et al , 2010, or indirect effects through climate-mediated changes in white-tailed deer distribution and transmission of deer parasites affecting moose survival (Lankester 2010). In terms of the first hypothesis, upper critical temperature limits (14°C in summer; -5°C in winter) can cause respiratory distress and other physiological responses in captive moose (Renecker and Hudson 1986) and logically such effects should translate to lower viability of free-ranging individuals.…”
Section: Population Demography In Ontariomentioning
confidence: 99%
“…Moose populations have recently declined dramatically in parts of the southern distribution, including areas from North Dakota to Nova Scotia, coincident with some combination of increased temperature and growing deer density [13,17]. Moose have also declined where deer are not present, on Isle Royale in Lake Superior [17], and where deer are present but climate has been relatively stable, in Nova Scotia [18].…”
Section: Herbivore Dynamics In a Changing Climate (A) Deer Replace Moosementioning
confidence: 99%
“…In Alaska, earlier onset of plant emergence from warmer springs reduced calving success in caribou (Rangifer tarandus), due to trophic and spatial asynchrony (Post et al 2008). Adult survival rates in moose (Alces alces) decreased with increasing ambient temperatures, resulting in lower moose densities, and ultimately, a northward shift in the southern boundary of their distribution (Lenarz et al 2009, Dou et al 2013. Lastly, in a study encompassing 16 populations of seven ungulates, Post and Stenseth (1999) revealed that large-scale climatic variability influenced growth, development, and fecundity of these species, which led to declines in 14 of the populations.…”
Section: Introductionmentioning
confidence: 99%